Endoscopic Management of Idiopathic Subglottic Stenosis: Factors Affecting Inter-Dilation Interval. (February 2017) - Shabani, Sepehr; Hoffman, Matthew R.; Brand, William T.; Dailey, Seth H.
Objective: To describe a homogeneous idiopathic subglottic stenosis (ISS) population undergoing endoscopic balloon dilation and evaluate factors affecting inter-dilation interval (IDI). Methods: Retrospective review of 37 patients. Co-morbidity prevalence versus normal population was evaluated using chi-square tests. Correlations were evaluated using Pearson product moment tests. Independent samples t tests/rank sum tests assessed differences between groups of interest. Results: All patients were female aged 45.9 ± 15.4 years at diagnosis. Four required a tracheotomy during management. Most prevalent co-morbidity was gastroesophageal reflux disease (GERD) (64.9%; P = .036). Body mass indices (BMI) at first and most recent dilation were 29.8 and 30.8 ( P = .564). Degree of stenosis before first dilation was 53 ± 14%. Patients underwent 3.8 ± 1.8 dilations (range, 1-11). Average IDI was 635 ± 615 days (range, 49-3130 days), including 556 ± 397 days for patients receiving concomitant steroid injection and 283 ± 36 for those who did not ( P = .079). Inter-dilation interval was not correlated with BMI ( r = 0.0486; P = .802) or number of co-morbidities ( r = −0.225, P = .223). Conclusions: Most patients with ISS can be managed endoscopically, and IDI may be increased with steroid injection. Gastroesophageal reflux disease is a common co-morbidity. Body mass index did not change over time despite potential effects on exercise tolerance; BMI did not affect IDI. Methods to determine optimal timing for next intervention are warranted.